2005
DOI: 10.1207/s15326942dn2702_5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Heterogeneity in Williams Syndrome

Abstract: This study used the Woodcock-Johnson Tests of Cognitive Ability-Revised to investigate a wide range of cognitive abilities in people with Williams syndrome (WS). It involved a comparatively large sample of 31 people with WS, but took a case-series approach. The study addressed the widespread claims of a characteristic "WS cognitive profile" by looking for heterogeneity rather than homogeneity. People with WS showed a variety of preserved (significantly above mental age [MA]), expected (at MA), and significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 72 publications
5
82
0
2
Order By: Relevance
“…As hypothesised, levels of elevated anxiety in WS, specifically generalised anxiety were associated with reduced fixation to the eye region and prolonged fixation to the mouth region of fearful faces. These findings extend previous studies which have demonstrated substantial heterogeneity in the social profile in WS (Jarvinen-Pasley et al, 2010;Hanley et al, in press;Porter & Coltheart, 2005), and suggest that heightened anxiety may influence attentional allocation and avoidance processing of socially meaningful stimuli in some individuals with WS.…”
Section: Discussionsupporting
confidence: 89%
“…As hypothesised, levels of elevated anxiety in WS, specifically generalised anxiety were associated with reduced fixation to the eye region and prolonged fixation to the mouth region of fearful faces. These findings extend previous studies which have demonstrated substantial heterogeneity in the social profile in WS (Jarvinen-Pasley et al, 2010;Hanley et al, in press;Porter & Coltheart, 2005), and suggest that heightened anxiety may influence attentional allocation and avoidance processing of socially meaningful stimuli in some individuals with WS.…”
Section: Discussionsupporting
confidence: 89%
“…These findings support studies which have demonstrated heterogeneity in WS (Järvinen-Pasley et al, 2010;Porter et al, 2007;Stojanovik, Perkins & Howard, 2006;Porter & Coltheart, 2005). Interestingly there was variability in age and IQ within clusters, indicating that developmental variables did not consistently or reliably predict RUNNING HEAD: Social Approach in Williams syndrome 19 SAB profiles.…”
Section: Heterogeneity In Wssupporting
confidence: 83%
“…Many developmental disorders are heterogeneous (Abrahams & Geschwind, 2008) and this is a particularly pertinent feature of WS, with cognitive, social, genetic and physical characteristics varying considerably from one individual to the next (Porter & Coltheart, 2005). Porter and Coltheart, (2005) challenged the notion of a "syndrome specific" (Howlin, Davies & Udwin, 1998) WS cognitive profile and suggested that subgroups might exist within WS based on their similarities in cognitive profile. They discovered evidence for two groups differing in terms of perception, attention and spatial construction abilities and differences in social-emotion skills.…”
Section: Heterogeneity Of Social Behaviours In Williams Syndromementioning
confidence: 99%
“…Perhaps not surprising given predictable large individual differences within neurodevelopmental disorders, indeed considering the cognitive heterogeneity we 14 know to be associated with WS (Porter, & Coltheart, 2005) the hit rate was low (48% WS vs 93% CA vs 79% over 65yrs) and the standard deviation was high (28%). Regarding our analysis of variability in response times during the duration of the task it is evident that WS participants were unable to exert controlled processes to maintain focus during the task.…”
Section: Discussionmentioning
confidence: 97%
“…Individuals with the disorder tend to function within the mild-moderate range of intellectual difficulty (Searcy et al, 2004) and exhibit a cognitive profile of relative proficiency within the verbal compared to the nonverbal domain (Bellugi, Lichtenberger, Mills, Galaburda, & Korenberg, 1999). The cognitive profile of the disorder has attracted the attention of cognitive scientists for the last two decades due to this juxtaposition of relatively better verbal than non-verbal skill, but it is critical to emphasise that heterogeneity of cognitive function occurs (Porter, & Coltheart, 2005) and the relative difference between verbal and spatial skill co-exists against a background of mild-moderate intellectual difficulty. Within the cognitive profile, research has recently highlighted the importance of exploring the area of executive functioning (e.g.…”
Section: Introductionmentioning
confidence: 99%